PENGARUH MEDIA PEMBELAJARAN TERHADAP MUTU PEMBELAJARAN PADA SEKOLAH DASAR TERAKREDITASI A - Sunaengsih, Cucun (Mimbar Sekolah Dasar, 2016)
The purpose of this study was to reveal and analyze the effect on the quality learning of learning media in an accredited “A” school. The method used in this research is a survey research with quantitative research approach. As for the population in this research is all teachers on the SDN Dr. Cipto Bandung. The results showed that the learning media influence the positive and significant impact on the quality of learning. The description of learning media show good results. So even with a description of the quality of learning has shown good results, as well as the correlation values for the quality of learning to learning media are in a strong position.Keywords: learning media, quality of learning, elementary school.